On the terminal homologation of physiologically active peptides as a means of increasing stability in human serum - Neurotensin, opiorphin, B27-KK10 epitope, NPY - Seebach, Dieter; Lukaszuk, Aneta; Patora-Komisarska, Krystyna; Podwysocka, Dominika; Gardiner, James; Ebert, Marc-Olivier; Reubi, Jean Claude; Cescato, Renzo; Waser, Beatrice; Gmeiner, Peter; Hübner, Harald; Rougeot, Catherine (Chemistry & Biodiversity, 2011)
The terminal homologation by CH insertion into the peptides mentioned in the title is described. This involves replacement of the N-terminal amino acid residue by a β - and of the C-terminal amino acid residue by a β -homo-amino acid moiety (β hXaa and β hXaa, resp.; Fig.1). In this way, the structure of the peptide chain from the N-terminal to the C-terminal stereogenic center is identical, and the modified peptide is protected against cleavage by exopeptidases (Figs.2 and 3). Neurotensin (NT; 1) and its C-terminal fragment NT(8-13) are ligands of the G-protein-coupled receptors (GPCR) NT1, NT2, NT3, and NT analogs are promising tools to be used in cancer diagnostics and therapy. The affinities of homologated NT analogs, 2b-2e, for NT1 and NT2 receptors were determined by using cell homogenates and tumor tissues (Table.1); in the latter experiments, the affinities for the NT1 receptor are more or less the same as those of NT (0.5-1.3 vs. 0.6nM). At the same time, one of the homologated NT analogs, 2c, survives in human plasma for 7 days at 37° (Fig.6). An NMR analysis of NT(8-13) (Tables.2 and 4, and Fig.8) reveals that this N-terminal NT fragment folds to a turn in CD OH. - In the case of the human analgesic opiorphin (3a), a pentapeptide, and of the HIV-derived B27-KK10 (4a), a decapeptide, terminal homologation (→3b and 4b, resp.) led to a 7- and 70-fold half-life increase in plasma (Fig.9). With N-terminally homologated NPY, 5c, we were not able to determine serum stability; the peptide consisting of 36 amino acid residues is subject to cleavage by endopetidases. Three of the homologated compounds, 2b, 2c, and 5c, were shown to be agonists (Fig.7 and 11). A comparison of terminal homologation with other stability-increasing terminal modifications of peptides is performed (Fig.5), and possible applications of the neurotensin analogs, described herein, are discussed. Copyright © 2011 Verlag Helvetica Chimica Acta AG, Zürich.